Analisis Yuridis Tentang Efektivitas Komnas HAM dalam Penegakkan Hak Asasi Manusia Di Indonesia - Muhammad Fajar Lutfi Raihan; Muhammad Azka Zidane; Hendra Anie (GLOBAL SCIENTS PUBLISHER, 2025)
This study analyzes the effectiveness of the National Commission on Human Rights (Komnas HAM) in enforcing human rights (HAM) in Indonesia from a normative juridical perspective. The background highlights ongoing human rights violations up to 2024-2025, such as torture, conflicts in Papua, and religious intolerance, impacting public trust, national integration, and international image. Employing a normative juridical method with primary data (legislation) and secondary data (legal literature), the research identifies major obstacles including limited authority of Komnas HAM (investigation only, not prosecution), weaknesses in procedural law (application of KUHAP unsuitable for gross violations), poor inter-institutional coordination (